THE URGENCY OF UPDATING REGULATIONS ON THE PROHIBITION OF DISCRIMINATION IN THE LABOR RECRUITMENT PROCESS: ITS IMPACT ON ECONOMIC GROWTH - Jason Christoff Tanuwijaya (RADJA PUBLIKA, 2026)
This study discusses the urgency of reforming regulations regarding the prohibition of discrimination in the labor recruitment process in Indonesia and its impact on economic growth. Discrimination in recruitment—such as restrictions based on age, gender, physical condition, and religion—remains prevalent despite the existence of various legal instruments prohibiting such practices, including ILO Convention No. 111, Law No. 13 of 2003 on Manpower, and the Circular Letter of the Minister of Manpower No. M/6/HK.04/V/2025. This research employs a normative juridical method with an interdisciplinary approach, combining legal and economic analysis to understand the consequences of discrimination more comprehensively. The findings show that the existing regulations lack sufficient legal force to effectively curb discriminatory practices, as circular letters are administrative in nature and not legally binding. From an economic perspective, discrimination in recruitment creates barriers to human capital accumulation, which ultimately reduces labor market efficiency and hinders economic growth. Therefore, a more stringent and legally binding regulatory reform is needed to ensure equal employment opportunities and promote inclusive economic growth.